Supplementation Effect of a Combination of Olive (Olea europea L.) Leaf and Fruit Extracts in the Clinical Management of Hypertension and Metabolic Syndrome - Michel P. Hermans; Philippe Lempereur; Jean-Paul Salembier; Nathalie Maes; Adelin Albert; Olivia Jansen; Joël Pincemail (MDPI AG, 2020)
Background: The role of herbal products in the prevention of cardiovascular disease requires supporting evidence. This open pilot study assessed the effect of 2-month supplementation of a combination of olive leaf and fruit extracts (Tensiofytol®, Tilman SA, Baillonville, Belgium) in the clinical management of hypertension and metabolic syndrome (MetS). Methods: A total of 663 (pre)-hypertensive patients were enrolled by general practitioners and supplemented for two months with Tensiofytol®, two capsules per day (100 mg/d of oleuropein and 20 mg/d of hydroxytyrosol). Systolic and diastolic blood pressures (SBP/DBP) were measured before and after treatment. Markers of MetS, high-density lipoprotein cholesterol (HDL-C), triglycerides (TG), fasting blood glucose (FG) and waist circumference (WC), were also examined. Results: Significant reductions (p < 0.0001) in SBP/DBP (13 ± 10/7.1 ± 6.6 mmHg) were observed and similarly in pre-diabetic and diabetic patients. Improvements in SBP/DPB were independent of age and gender but greater for elevated baseline SBP/DBP. Tensiofytol® supplementation also significantly improved markers of MetS, with a decrease of TG (11%), WC (1.4%) and FG (4.8%) and an increase of HDL-C (5.3%). Minor side effects were reported in 3.2% patients. Conclusions: This real-life, observational, non-controlled, non-randomized pilot study shows that supplementation of a combination of olive leaf and fruit extracts may be used efficiently and safely in reducing hypertension and MetS markers.